A survey of correlations for heat transfer and pressure drop for evaporation and condensation in plate heat exchangers. (May 2016) - Eldeeb, Radia; Aute, Vikrant; Radermacher, Reinhard
Highlights: Comprehensive review of heat transfer and pressure drop correlations during boiling and condensation in plate heat exchangers. Numerical comparison of such correlations for Ammonia, R410A as well as other lower GWP alternatives. Review of current status and identified gaps in the literature and potential research avenues. All correlations with their respective range of applicability are summarized. Abstract: Plate Heat Exchangers (PHEs) are used in a wide variety of applications including heating, ventilation, air-conditioning, and refrigeration. PHEs are characterized by compactness, flexible thermal sizing, close approach temperature, and enhanced heat transfer performance. Due to their desirable characteristics, they are increasingly utilized in two-phase flow applications. Detailed research on heat transfer and fluid flow characteristics in these types of exchangers is required to design and use plate heat exchangers in an optimal manner. This paper reviews the available literature on the correlations for heat transfer and pressure drop calculations for two-phase flow in PHEs as an initial process step in order to understand the current research status. Comparative evaluations for some of the existing correlations are presented in the light of their applicability to different refrigerants. Overall, there is a significant gap in the literature regarding two-phase heat transfer and fluid flow characteristics of these types of exchangers.